Typification and taxonomic remarks on some names in Phlomoides (Phlomideae: Lamiaceae) - Almasi, Maryam; Salmaki, Yasaman; Xiang, Chun-Lei (Phytotaxa, 2022)
The genus Phlomoides (Lamiaceae, tribe Phlomideae) has been recently re-circumscribed to include members of Eremostachys and a few other genera. As a consequence, several new combinations and new names have been suggested in this genus recently. Here, typification of 14 names in Eremostachys, viz. E. adpressa, E. alberti, E. boissieriana, E. czuiliensis, E. eriocalyx, E. gymnocalyx, E. hissarica, E. iliensis, E. laciniata var. labiosiformis, E. sarawschanica, E. speciosa var. schugnanica, E. subspicata, E. trautvetteriana and E. zenaidae is presented. Moreover, two new combinations (Phlomoides calophyta and P. transjordanica) and two new synonyms (P. kermanica and P. semnanensis) are proposed.